Desarrollo de un medio digital para contribuir a la difusión de contenidos del movimiento de mujeres de El Oro. - Moreira Torres, Gabriela Lisbeth (2017)
The alternative means of communication have come to provide a space in which information is disseminated without restriction as in a traditional medium, since these have their own interests. In this century, the internet has revolutionized communication, forcing the communicators to adapt to the changes that it brings, together allows the interaction between the sender and receiver, in addition to that any ordinary citizen becomes an information agent. Due to their immediacy, they have the advantage that information reaches an indeterminate public in different parts of the world, which is not the case with traditional media, although many have already adapted to the digital age. The Women's Movement of El Oro is a non-profit institution that provides social services to the province, but does not have the necessary reception in the community. The traditional means of information do not provide the opportune space for the dissemination of the work carried out by the feminist group, hence the need to create a website for the Women's Movement of El Oro and thus have a space of their own. In this platform was designed sections of contacts, news, real stories of violence, your rights, gallery and the history of the MMO.